2006
DOI: 10.1038/sj.eye.6702451
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of epilenticular IOL implantation vs technique of anterior and primary posterior capsulorhexis with anterior vitrectomy in paediatric cataract surgery

Abstract: Purpose To compare the functional outcome of epilenticular intraocular lens (IOL) implantation vs the technique of anterior continuous curvilinear capsulorhexis (ACCC), posterior continuous curvilinear capsulorhexis (PCCC) with vitrectomy and in-the-bag IOL implantation in paediatric cataract surgery. Methods Forty eyes of 33 children with developmental or traumatic cataract, whose mean age was 2-12 years, were randomly divided into two groups A and B. Group A patients underwent epilenticular IOL implantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…[ 16 ] and Rastogi et al . [ 17 ] They reported similar results, but only in pediatric subjects; furthermore, no control group was included. Shah et al .…”
Section: Discussionmentioning
confidence: 79%
“…[ 16 ] and Rastogi et al . [ 17 ] They reported similar results, but only in pediatric subjects; furthermore, no control group was included. Shah et al .…”
Section: Discussionmentioning
confidence: 79%
“…[15] Another study from India comparing traumatic cataract surgery with and without posterior capsule management had demonstrated that AV + PPC had a beneficial effect on visual acuity ( P = 0.001) and prevented further intervention. [19] This study showed that a significant number of children with intact posterior capsule may develop visually significant PCO even after placement of square-edge IOL in the capsular bag. Eyes with PCO in our study had similar vision than those without, as PPC + AV was done in very young children who had poorer vision.…”
Section: Discussionmentioning
confidence: 97%
“…35,36 Several studies have assessed the efficacy of posterior capsulectomy and anterior vitrectomy in pediatric TC and reported a positive effect on the visual outcomes. [48][49][50][51][52] Hence, performing posterior capsulectomy during surgery is recommended in children. This is not just because of the elevated risk of secondary visual axis opacification development in children, who might not be cooperative for a postoperative YAG capsulectomy (YLC), but also because of the presence of an exceptionally dense capsular membrane.…”
Section: Management Strategiesmentioning
confidence: 99%